Post‐Assembly Stabilization of Rationally Designed DNA Crystals1. (1st July 2015) - Zhao, Jiemin; Chandrasekaran, Arun Richard; Li, Qian; Li, Xiang; Sha, Ruojie; Seeman, Nadrian C.; Mao, Chengde
Abstract This manuscript reports an effort to stabilize self‐assembled DNA crystals. Owing to their weak inter‐unit cohesion, self‐assembled DNA crystals are fragile, which limits the potential applications of such crystals. To overcome this problem, another molecule was introduced, which binds to the cohesive sites and stabilizes the inter‐unit interactions. The extra interactions greatly improve the stability of the DNA crystals. The original DNA crystals are only stable in solutions of high ionic strength (e.g., ≥1.2 M (NH4)2SO4); in contrast, the stabilized crystals can be stable at ionic strengths as low as that of a 0.02 M solution of (NH4)2SO4. The current strategy is expected to represent a general approach for increasing the stability of self‐assembled DNA nanostructures for potential applications, for example, as structural scaffolds and molecular sieves.